Landscape-Scale Land-Cover Change and Long-Term Abundance of Scaled Quail and Northern Bobwhite in Texas - Andrew S. Bridges; Markus J. Peterson; Nova J. Silvy; Fred E. Smeins; X. Ben Wu (National Quail Symposium Proceedings, 2017)
Between 1978 and 1998, scaled quail (Callipepla squamata) abundance in the Rolling Plains ecological region declined (r1 = -0.85, P < 0.001), while no trend (P = 0.74) was exhibited in the South Texas Plains. Northern bobwhites (Colinus virginianus) exhibited no trend (P > 0.10) in either ecological region. Changes in land-cover between 1976 and 1998 indicated a loss of Savannah and Shrubland and an increase in Parkland cover types in the Rolling Plains. In the South Texas Plains, Woodland and Brush/Shrubland decreased between 1976 and 1998, whereas Brush/Shrub Parkland and Parkland increased. We examined land-cover change as a possible component in the scaled quail decline in the Rolling Plains. Loss of the Shrubland cover type may explain the decline of scaled quail in the Rolling Plains. Our results further suggest intraspecific spatial usability boundaries. These boundaries differed by species, with scaled quail associated with dense structure near the ground, whereas northern bobwhite were less abundant in areas dominated by scattered shrubs and trees, and large expanses of short, close-canopy cover types. A method is proposed for quickly obtaining data on land-cover changes on time.
Keywords: Callipepla squamata; Colinus virginianus; habitat; land-cover; northern bobwhite; regional abundance; scaled quail; Texas